Optimized Model of Cerebral Ischemia In situ for the Long-Lasting Assessment of Hippocampal Cell Death - Rybachuk, Oksana; Kopach, Olga; Krotov, Volodymyr; Voitenko, Nana; Pivneva, Tatyana (Frontiers in Neuroscience, 2017)
Among all the brain, the hippocampus is the most susceptible region to ischemic lesion, with the highest vulnerability of CA1 pyramidal neurons to ischemic damage. This damage may cause either prompt neuronal death (within hours) or with a delayed appearance (over days), providing a window for applying potential therapies to reduce or prevent ischemic impairments. However, the time course when ischemic damage turns to neuronal death strictly depends on experimental modelling of cerebral ischemia and, up to now, studies were predominantly focused on a short time-window ¬– from hours to up to a few days post-lesion. Using different schemes of oxygen-glucose deprivation (OGD), the conditions taking place upon cerebral ischemia, we optimized a model of mimicking ischemic conditions in organotypical hippocampal slices for the long-lasting assessment of CA1 neuronal death (at least three weeks). By combining morphology and electrophysiology, we show that prolonged (30-min duration) OGD results in a massive neuronal death and overwhelmed astrogliosis within a week post-OGD whereas OGD of a shorter duration (10-min) triggered programmed CA1 neuronal death with a significant delay – within 2 weeks – accompanied with drastically impaired CA1 neuron functions. Our results provide a rationale towards optimized modelling of cerebral ischemia for reliable examination of potential treatments for brain neuroprotection, neuro-regeneration or testing neuroprotective compounds in situ.